Analisis Yuridis Terhadap Penjatuhan Pidana Tambahan Pencabutan Hak Memilih dan Dipilih Dalam Jabatan Publik Djoko Susilo - Aji Lukman Ibrahim (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2014)
In against the corruption crime, it must be established the distinct sanctions inorder to provide a deterrent effect to the corruptor and it is expected to decrease acorruption crime for the others. One of the ideas is applying expropriation as theadditional punishment. Djoko Susilo was first convicted criminal sentenced to haveexpropriation to vote and be elected rights in public official. The additional punishmentof expropriation for corruption is still relatively new and it is interesting to study. Onthis study is about the compatibility of expropriation to vote and be elected DjokoSusilo’s case in the public official on criminal code section 38 and how it is viewed fromthe perspective of human rights. This study uses normative juridical approach on theconstitution then compared with the additional punishment of expropriation to vote andbe elected Djoko Susilo’s case in the public official. It has occurred misconduct ofhandedness because revoke the rights to vote and be elected in Djoko Susilo’s case inpublic official without limiting it within a certain period as set out on criminal codesection 38. The rights to vote and be elected in public office is a part of human rights,then revoke, eliminate or negate the human rights even though through the verdict is ahuman rights violation.